Investment capital mobilization and sustainable economic development: From theory to practice in Vietnam's Southern Key Economic Region - Nguyen, Chí Công; Le, Hoàng Anh (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2022)
The article used the method of content - analysis to synthesize and systematize international experiences on mobilizing investment capital for regional economic development; At the same time, combined with statistical method and synthesize data on investment capital mobilization and Socioeconomic development of the Southern Key Economic Region, are published in the Statistical Yearbooks of the Provinces/City, the General Statistics Office of Vietnam and the securities company. Based on the statistical data, the authors have studied the actual situation of mobilizing capital investment in the Southern Key Economic Region in the period 2005-2018 according to four main capital supply channels: foreign direct investment (FDI), nonstate investment sector, household capital, the State investment sector. Through analyzing the actual situation of mobilizing capital investment in the region, the article suggested some solutions to support attracting investment capital in the Southern Key Economic Region.